2020
DOI: 10.1097/ccm.0000000000004518
|View full text |Cite|
|
Sign up to set email alerts
|

Hysteresis and Lung Recruitment in Acute Respiratory Distress Syndrome Patients: A CT Scan Study*

Abstract: Objectives: Hysteresis of the respiratory system pressure-volume curve is related to alveolar surface forces, lung stress relaxation, and tidal reexpansion/collapse. Hysteresis has been suggested as a means of assessing lung recruitment. The objective of this study was to determine the relationship between hysteresis, mechanical characteristics of the respiratory system, and lung recruitment assessed by a CT scan in mechanically ventilated acute respiratory distress syndrome patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The key to reaching this balanced state is to perform adequate recruitment maneuvers based on lung physiology, 15 increasing airway pressures until reaching critical lung opening pressure and then decreasing them while maintaining the optimal lung volume and before reaching the critical lung closing pressure. In this situation the hysteresis of the respiratory system allows ventilation in the deflation limb of the pressure–volume curve 22 which provides optimal volumes and minimal distending pressure, avoiding both overdistension and atelectasis. This phenomenon has been extensively studied in conventional ventilation and probably provides a similar benefit when ventilating patients in HFOV 13 …”
Section: Discussionmentioning
confidence: 99%
“…The key to reaching this balanced state is to perform adequate recruitment maneuvers based on lung physiology, 15 increasing airway pressures until reaching critical lung opening pressure and then decreasing them while maintaining the optimal lung volume and before reaching the critical lung closing pressure. In this situation the hysteresis of the respiratory system allows ventilation in the deflation limb of the pressure–volume curve 22 which provides optimal volumes and minimal distending pressure, avoiding both overdistension and atelectasis. This phenomenon has been extensively studied in conventional ventilation and probably provides a similar benefit when ventilating patients in HFOV 13 …”
Section: Discussionmentioning
confidence: 99%
“…However, compliance might be more related to the improvement or deterioration of already ventilated lung units than the actual recruitment of atelectatic lung units ( 58 ). In a human study, a strong correlation was found between the amount of potentially recruitable lung tissue on CT-scan and pressure-volume loop parameters (hysteresis ratio and maximum normalized distance) in patients with early stages of ARDS ( 59 ). However, these strategies for assessing pulmonary recruitability have been performed under static conditions (low-flow method) that require deep sedation or paralysis, which is a potential limitation to the use of this technique ( 59 ).…”
Section: Methods To Assess the Effects Of Recruitment Maneuversmentioning
confidence: 99%
“…However, anatomical recruitment as measured with computed tomography, and oxygenation (termed functional recruitment) have been shown to be poorly correlated with each other ( 58 ). Indeed, incremental PEEP during a recruitment maneuver might affect oxygenation by mechanisms other than non-aerated tissue recruitment, such as changes in cardiac output and blood flow distribution in the lungs ( 58 , 59 ). Improved lung compliance at higher pressures may reflect both improved mechanical properties of already open lung units and recruitment of previously collapsed alveoli ( 39 ).…”
Section: Methods To Assess the Effects Of Recruitment Maneuversmentioning
confidence: 99%
“…If the PEEP step method is implemented in a ventilator, it can be programmed to make a PEEP-down procedure from a high initial PEEP level as prolonged expirations step-wise down to lower PEEP levels, which will make the procedure very rapid. However, such a procedure needs to be evaluated as hysteresis phenomenon during fast procedures may cause less adequate results [40][41][42].…”
Section: Methodological Considerationsmentioning
confidence: 99%